Switzerland : 2002 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the economy of Switzerland cooled in 2001 as business investment fell and exports were hit by the global slowdown and an appreciation of the Swiss franc. Real GDP growth dropped to 1.3 percent, unemployment edged up, and the external current account surplus declined to 10 percent of GDP. The IMF staff projects that real GDP will grow by just under 1 percent in 2002 on the back of a global recovery in the second half of the year and effects of the monetary easing in 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet